Pangium edule reinw: A promising non-edible oil feedstock for biodiesel production - Atabani, A.E.; Badruddin, I.A.; Masjuki, Haji Hassan; Chong, W.T.; Lee, K.T. (2015)
Biodiesel production from non-edible feedstocks is currently drawing much attention due to legitimate concerns about the effects of using edible oil for fuel. Pangium edule Reinw is a non-edible feedstock. Pangium is a tall tree native to the Micronesia, Melanesia and the mangrove swamps of South-East Asia. In this study, biodiesel production and characterization from P. edule oil was reported. The seeds were obtained from Bogor, Indonesia. The oil was found to have an acid value of 19.62 mg KOH/g oil. Therefore, a two-step acid-base-catalysed transesterification was used to produce biodiesel. This was followed by evaluating the physical and chemical properties of biodiesel and its blends with diesel. It has been found that the determined properties of P. edule methyl ester indicate that the oil can be considered as a future biodiesel source. The most remarkable feature of P. edule is its cloud, pour and cold filter plugging points. This biodiesel yielded cloud, pour and cold filter plugging points of -6, -4 and -8 A degrees C, respectively. This indicates the viability of using this biodiesel in cold countries. Therefore, it is suggested that more research should be conducted on P. edule for future biodiesel production.